2018
DOI: 10.1021/acs.joc.8b02076
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Synthesis of N-Substituted peri-Xanthenoxanthene Diimide (PXXDI) and Monoimide (PXXMI) Scaffolds

Abstract: The tailored synthesis of homo (A2) and hetero (AB) N-substituted peri-xanthenoxanthene diimides (PXXDIs) and peri-functionalized PXX monoimides (PXXMIs) from 3-hydroxy naphthalic anhydride is described. As A2-type PXXDIs could be synthesized in one step, AB-type PXXDIs and PXXMIs were prepared through a modular approach capitalizing on sequential Suzuki coupling, Imidation and Pummerer reactions with very high yields. In view of their potential applications as organic semiconductors, self-organization studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…The synthetic route is outlined in Chart 1. Substituted 2-naphthol underwent self-coupling or cross-coupling reactions to obtain the target products via solid-phase carbon-bath microwave method 15) in the presence of copper acetate. The reaction was fast and took only 6 to 12 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthetic route is outlined in Chart 1. Substituted 2-naphthol underwent self-coupling or cross-coupling reactions to obtain the target products via solid-phase carbon-bath microwave method 15) in the presence of copper acetate. The reaction was fast and took only 6 to 12 min.…”
Section: Resultsmentioning
confidence: 99%
“…But the maximum absorption wavelength of PXX can reach more than 600 nm after structural modification. 16) So PXX still has application prospects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the synthetic methods toward the peri -xanthenoxanthene diimide 135.4a , a direct oxidative Pummerer dimerization was examined ( Scheme 135 ). 272 The homocoupling of 135.5 was done in up to 43% yield in the presence of CuCl in DMSO under air. An alternative pathway toward 135.4a and related compounds was also described in the same study.…”
Section: Pyrenoidsmentioning
confidence: 99%
“…[79,80] Recently, our group has gone on to expand the library of Odoped PAHs through the development of Cu-catalysed intramolecular etherification reactions. [81][82][83][84][85][86] For instance, we have demonstrated that smaller O-doped molecules containing furanyl, pyranyl, and oxepinyl moieties could be easily accessed through CuO-mediated Pummerer-type oxidative cyclisation. [87] In these works, it has been shown that the formation of pyrano rings provokes a rise of the HOMO energy level, which results in a shrinking of the HOMO-LUMO gap and in the lowering of the oxidation potential.…”
Section: Introductionmentioning
confidence: 99%